Whole life energy rating for buildings Structural and Building Board half day meeting : Thursday 13th February 1997 2.00 pm - 5.00 pm. (Thomas Telford, 1997)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a half-day meeting held on 13 February 1997.